Praksis Pembelajaran Kewirausahaan pada Unit Produksi Jasa Boga - Aida Lasmi; Zuhrinal M. Nawawi (MES Management Journal, 2022)
The Praxis of Entrepreneurship Learning in the Food services Production Unit. This study aims to investigate teachers’ concepts of entrepreneurship learning, entrepreneurship competencies developed in the production unit, and entrepreneurship learning processes in the production unit of food services in SMK Negeri 6 Yogyakarta. This study employed the qualitative case study. The research subjects were the principal, head of the study program, head of the production unit, and students. Data were collected through interviews, observations, and documentation. The collected data were analyzed using Miles and Huberman model consisting of data reduction, data display, and conclusion. The result shows that: (1) Entrepreneurship learning needs hands-on-experiences-based; (2) the entrepreneurship competency developed through the production unit includes a) entrepreneurship knowledge, consisting of self-knowledge and practical knowledge, b) entrepreneurship attitudes, consisting of work ethos, autonomy, discipline, creativity, and innovativeness, and c) entrepreneurship skills, consisting of: technical skill, human relations skill, conceptual skill, decision making skill, time management skill, and leadership skill; (3) no instructional standard employed in to develop entrepreneurship in production unit. There are three entrepreneurship learning models employed in the production unit: inside production, outside production, and mobile canteen. The learning outcome is measured in two ways, i.e. performance and product monitoring. Meanwhile, evaluation of the students’ learning progress is conducted by using profit-based evaluation. Keywords: learning, entrepreneurship, production unit